1996
DOI: 10.1002/(sici)1096-8628(19961016)65:2<97::aid-ajmg1>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Retinitis pigmentosa in a young man with Noonan syndrome: Further evidence that Noonan syndrome (NS) and the cardio-facio-cutaneous syndrome (CFC) are variable manifestations of the same entity?

Abstract: We report on a young man with Noonan syndrome (NS) and retinitis pigmentosa. As far as we know, retinitis pigmentosa has not been reported in NS. However, in the 3 cardio‐facio‐cutaneous syndrome (CFC) patients in whom electroretinographic studies were performed, retinal anomalies have been found. In addition, decreased vision, refractive errors, strabismus, and optic disc anomalies were reported in CFC patients. This observation suggests that NS and CFC are variable manifestations of the same entity. © 1996 W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
1
13
0
1
Order By: Relevance
“…However, present and previous data indicate that in several cases CFC syndrome is a severe expression of NS. [5][6][7] We hypothesize that CFC syndrome is related to NS, either as an allelic variant or as a disorder with a similar molecular and cellular pathogenic mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, present and previous data indicate that in several cases CFC syndrome is a severe expression of NS. [5][6][7] We hypothesize that CFC syndrome is related to NS, either as an allelic variant or as a disorder with a similar molecular and cellular pathogenic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 NS and CFC syndrome can result from different mutations or deletions in the same 5 cM chromosomal region in 12q24. In the reported family, however, the variable expression of the phenotype resulted in NS in some individuals and CFC syndrome in others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional reports soon followed and, according to a recent review, 2 about 59 patients have been reported, providing the basis for an accurate delineation of the phenotypic spectrum of the syndrome. Nevertheless, a question has lingered for many years whether CFC is a unique and separate condition, or a variant of the Noonan syndrome (OMIM 163950) [3][4][5][6][7][8][9] or of the Costello syndrome (OMIM 218040). 10 These three conditions share several manifestations (table 1) [11][12][13] and ''borderline'' cases do exist, usually in infants, which defy a clear-cut diagnosis.…”
mentioning
confidence: 99%
“…In 1991, Fryer et al suggested the existence of a phenotypic overlap between CFC and Noonan syndrome (NS) and several authors reporting this condition supported their view (Bottani et al 1991;Ward et al 1994;Krajewska-Walasek et al 1996;Leichtman 1996;Lorenzetti and Fryns 1996). These authors suggested that both CFC and NS are probably a variable manifestation of the same clinical and aetiological entity and that they might arise from the expression of molecular defects in a common gene.…”
Section: Introductionmentioning
confidence: 99%